PERANAN GURU DALAM MENANGGULANGI KENAKALAN SISWA DI SMA NEGERI 3 TAPUNG KABUPATEN KAMPAR - saputra, Rosi priasdi; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is reviewed by teachers in adolescent development and in the implementation of globalization. Once the author took the title "The Role of Teacher In cope with Juvenile Delinquency in Senior High School (SMA) Negeri 3 Tapung Kampar District". The formulation of the problem in this research is How the role of teachers in tackling juvenile delinquency of students of SMA Negeri 3 Tapung? The purpose of this study is to determine the role of teachers in tackling juvenile delinquency of students of SMA Negeri 3 Tapung according to the perspective of teachers and to know the role of teachers in tackling juvenile delinquency of students of SMA Negeri 3 Tapung according to student perspective. The population of this study are all teachers of SMA Negeri 3 Tapung that require 31 people and 2nd grade students of SMA Negeri 3 Tapung with population 210 people, and taken 31 people as sample with propotional random sampling technique. Data collected through observation, questionnaires, documentation and literature study. In analyzing the data, using qualitative descriptive analysis. The formulation of the hypothesis formulated is "teacher learning in cope with juvenile delinquency in SMA Negeri 3 Tapung" is "Very Good".The results of this study indicate the role of teachers in tackling juvenile delinquency in SMA 3 Tapung according to the perspective of teachers, seen from the percentage of 31 respondents teachers stated 27.59% for the category very often, 57.26% for the category often, 14.64% for the category sometimes , And 0.48% for the category never. And according to the perspective of the 31 respondents stated 33.87% for the category very often, 54.03 for the frequent category, 6.4 for the occasional category, and 5.64 for the category never.Keywords: Teacher's Role, Cope withJuvenile Delinquency